A Note on Klb yārh in al-Bīrūnī’s Autobibliography - Kahl, Oliver (Arabica, 2024)
This short article proposes two possible explanations of the opaque term klb yārh (كلب ياره), which makes an isolated appearance in the autobibliography of Abū Rayḥān al-Bīrūnī (d. ca. 440/1048). There, it is registered as the title of an otherwise unknown Indian medical work which al-Bīrūnī himself says he translated from Sanskrit into Arabic.